Mobility intersections: social research, social futures. (7th August 2016) - Büscher, Monika; Sheller, Mimi; Tyfield, David
Abstract: This special issue seeks to deepen conversations at the intersections between mobilities research and a number of adjacent fields. Contributions explore how mobilities research has emerged and travelled along with a range of approaches concerned with the lived production of socio-material orders, such as science and technology studies, non-representational and feminist theory, critical and speculative design and cosmopolitanism, to name but a few, while also intersecting with many applied fields, such as transport planning and policy, disability studies, or disaster response. The field of mobilities research has grown by connecting different epistemological frames, and offering new post-disciplinary approaches to complex interconnected phenomena. In pausing to reflect on these mobility intersections, we suggest that mobilities research is integral to a broader project of transforming the social sciences that is currently underway.